Identification of genomic regions and candidate genes associated with growth of Eriocheir Sinensis by QTL mapping and marker annotation. (8th August 2015) - Hui, Min; Cui, Zhaoxia; Liu, Yuan; Song, Chengwen; Li, Yingdong; Shi, Guohui; Luo, Danli
Abstract: Eriocheir sinensis is a valuable economic fishery resource in Asia and an invasive species of the world. A genome‐wide quantitative trait loci (QTLs) scan for 10 growth traits was performed, resulting in 61 significant QTLs with phenotypic variance explained by a QTL from 11.2% to 42.2%. Most of the QTLs were restricted to narrow regions (<1 cM) and confirmed by genome wide association study. By blasting all markers on the linkage map with available transcriptomic and genomic sequences of E. sinensis, 15 markers on 14 linkage groups were found to be resided in gene sequences related to animal growth. A hypothetical protein gene (marker f1459) and a C‐type lectin domain family 2 member D3 (marker m44) gene were detected to be located within the QTL intervals on LG11 and LG57 respectively. In addition, marker f2745 on LG34 was identified to be within intron 2 of Molting‐inhibiting hormone 1, a moulting associated gene; two marker‐containing genes, Adenomatous polyposis coli protein and Proto‐oncogene tyrosine‐protein kinase ROS were detected to be located on LG21 and LG44, which were involved in the growth‐related pathways 'Wnt signaling pathway' and 'mitogen‐activated protein kinase signaling pathway' respectively. The results are expected to be useful in marker‐assisted selection and provide valuable information for the study of gene network regulation for growth of the crab.